KINDNESS STRATEGY : AN APPROACH TO BUILDING GOOD CHARACTER IN STUDENTS - Dian Prastiwi, Liyana; Anwar; Trias Puguh Jatmiko, Henry (Journal of Language Teaching Lingustics and Literature, 2025)
Building character and cultivating positive behavior is the main focus of education in the 21st century. One innovative approach that meets the challenges of the times is the application of kindness as a learning strategy. This study aims to explore the effectiveness of kindness- based learning strategies in shaping students' character and good habits. in a way general . The study used a descriptive qualitative approach to explore the implementation of the strategy The results of the study show that the implementation of kindness strategies through social projects, character literacy , and weekly reflective activities significantly shape attitudes sensitivity , concern , and closeness in a way emotional between students.